Membangun Kemandirian dan Efisiensi Ibu-Ibu PKK melalui Manajemen Waktu di Desa Kaligading - Alfin Muslikhun; Mukhlidin Mukhlidin; Rowiyani Rowiyani; Restu Carissa; Chelsea Olivia Fiqih Merisa (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
This community service program aims to enhance the independence and efficiency of PKK women in Kaligading Village through time management training. The main challenge faced by PKK members lies in balancing domestic, social, and economic roles, which often hinders optimal participation in village programs. The method applied was Participatory Action with a community development approach, involving 32 participants consisting of PKK administrators, dasa wisma leaders, and home-based business groups. The training covered the fundamentals of time management, priority setting, daily scheduling, and effective meeting simulations. The results revealed an 85% improvement in participants’ knowledge and skills as measured by post-test, accompanied by behavioral changes in utilizing simple tools such as daily notes and digital reminders. Participants successfully adopted new habits to balance family responsibilities, organizational duties, and entrepreneurial activities. Furthermore, the effectiveness of PKK meetings and programs increased, fostering greater participation and maximizing local potential. In the long term, this program contributes to strengthening PKK’s institutional capacity while opening opportunities for improving family economic welfare.